Knowledge, attitudes, and perceptions of long‐acting reversible contraceptive methods among healthcare workers in sub‐Saharan Africa. Issue 8 (28th April 2021) - Rouncivell, Laura; Takuva, Simbarashe; Ledibane, Neo; Musekiwa, Alfred; Leong, Trudy D
Abstract: Objective: To assess the knowledge, attitudes and perceptions (KAP) of long‐acting reversible contraceptive (LARC) methods among healthcare workers (HCWs) in sub‐Saharan Africa (SSA). Methods: A systematic review and meta‐analysis were conducted following the PRISMA method. Two authors independently searched three electronic databases for studies published between 2000 and January 2020 reporting on the KAP of LARC methods among HCWs in SSA. Titles and abstracts were screened against eligibility criteria, data were extracted and the included studies were assessed for risk of bias. A meta‐analysis of proportions for 11 pre‐determined questions relating to LARC KAP was performed. Heterogeneity was explored using the I 2 ‐statistic and publication bias investigated using funnel plots and Egger's tests. Results: Twenty‐two studies comprising 11, 272 HCWs from 11 SSA countries were included. 50% (95% CI: 34%, 67%) of HCWs had received intrauterine contraceptive device (IUCD) insertion training while 63% (95% CI: 44%, 81%) expressed a desire for training. Only 27% (95% CI: 18%, 36%) deemed IUCD appropriate for HIV‐infected women. Restrictions for IUCD and injectables based on a minimum age were imposed by 56% (95% CI: 33%, 78%) and 60% (95% CI: 36%, 84%), respectively. Minimum parity restrictions were observed among 29% (95% CI: 9%, 50%) of HCWs for IUCDs and 36% (95% CI: 16%, 56%) for injectable contraceptives. Heterogeneity was high and publication bias was present in two of the 11 questions. Conclusion: The systematic review and meta‐analysis indicate that unnecessary provider‐imposed restrictions may hinder the uptake of LARC methods by women in SSA.